Prognostic factors of papillary renal cell carcinoma: results from a multi-institutional series after pathological review - Herrmann, Edwin; Trojan, Lutz; Becker, Frank; Wülfing, Christian; Schrader, Andres J.; Barth, Peter; Stöckle, Michael; Hammerschmied, Christine G.; Staehler, Michael; Stief, Christian; Haferkamp, Axel; Hohenfellner, Markus; et al. (The journal of urology, 2010)
Purpose: - - We examined papillary renal cell carcinoma prognostic variables and validated the 2002 UICC TNM staging system in a multicenter analysis. - - Materials and Methods: - - From 10 urological institutions in Germany followup data were collected on a total of 675 patients with papillary renal cell carcinoma. Central pathological review was done to validate external histopathological diagnoses. The Kaplan-Meier method was used to derive cumulative cancer specific and overall survival, and the log rank test was used to compare the curves of 2 or more groups. For multivariate analysis of prognostic factors Cox regression analysis was done. All proportional hazard assumptions were systemically verified using the Grambsch-Therneau test. - - Results: - - Cancer specific survival was significantly related to TNM stage and histological grading on univariate and multivariate analyses. Five-year cancer specific survival in pT1b cases was significantly shorter than in pT1a cases (90.0% vs 98.3%, p = 0.017). No significant difference was found between pT1b and pT2 tumors. Patients with pT3 or greater disease were at high risk for metastasis (50.6%) while metastatic disease associated with pT2 or less tumors occurred in 7.8% (p <0.0001). After metastatic disease was present the prognosis was poor with 7.2% 5-year cancer specific survival. Age was associated with poor prognosis in the subgroup with pT3 or greater tumors on univariate analysis (p = 0.026) but not on multivariate analysis. - - Conclusions: - - In its current form the 2002 UICC TNM staging system is not applicable to papillary renal cell carcinoma. Clinical and radiological followup should be offered at frequent intervals to patients with venous thrombus and/or locally advanced disease. The role of age remains unclear but should not be underestimated in risk stratification after surgery.